Le radicalisme en Grande-Bretagne de 1815 à 1830 - Rémy Duthille (Revue Française de Civilisation Britannique)
Since E.P. Thompson’s classic The Making of the English Working Class (1963), the historiography of protest movements has considerably expanded. This article takes stock of recent reinterpretations of a period which Thompson saw as the heroic age of working-class radicalism. It discusses debates on the rise of the mass platform and the significance of Peterloo and the new emphasis on culture, gender, and micro-history to revise towering narratives. It also examines the Cato Street conspiracy (1820), and the studies placing it in British, imperial and international context. A section on Scotland rehearses the state of the debate on the 1820 ‘Radical War’ and Scottish specificities.